(3JNQjL GdOdGdGJ GdSeYjI Ydi eGcGf aj YgO QShd Gddg Udi Gddg Ydjg hSde ef GdMQa hGdUfGFY hGdeYGedGJ GdTQYjIs - (3Ydj Hf eMeO Hf CMeO Hf ehSi Hf eSYhOs ((3RjO GdeLjH eMeO CHj GdaJM Hf CMeO Hf eMeO GdNWjH GdWhNi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb ef ZjQ GaJbGQ Edjge s
(3BNQgG (B:s
(3ced LejYg hGdMeO ddg Ydi Pdc MeOkG cKjQkG s
(3ai Chd GdfSNI GVWQGH ai GdChQGbs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B6s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B58 s
Keywords: (3GdJGQjNs